Multiwall carbon nanotubes/lithium salts/polyethersulfone membrane for microalgae harvesting - Mohd. Khairuddin, Nur Farahah (2020)
Membrane filtration for microalgae harvesting has been hampered by bio-fouling. In this research work, feasibility of microalgae harvesting using good anti fouling polyethersulfone (PES) membranes was examined. The main objective of the study is to develop a high-performance membrane with anti-fouling effect for microalgae harvesting. The antifouling PES membranes were fabricated using PES, multiwall carbon nanotubes (MWCNT) and two different additives i) lithium bromide (LiBr) ii) lithium chloride (LiCl) in dimethylacetamide. PES/MWCNT is the control membrane. The membranes were prepared via two methods; non-solvent induced phase separation (NIPS) and thermally induced phase separation (TIPS). The membrane performances were evaluated in terms of membrane flux, molecular weight cut-off and fouling performances. The results show that the morphology of the hybrid PES/MWCNT/LiCl and PES/MWCNT/LiBr membranes were very much influenced by the phase separation method. Lithium salts helped to increase membrane porosity. Flux rates of the membranes were improved dramatically with increasing amount of additives when prepared using TIPS. Both NIPS and TIPS membranes can separate 100% of the microalgae. In terms of fouling propensity, TIPS membrane with LiCl exhibited more than 80% flux recovery while TIPS membrane with LiBr showed 100% flux recovery which exhibits excellent anti-fouling property. The membrane fabricated with 1 wt% MWCNT, 5 wt% LiBr and 18 wt% PES via TIPS process possessed an excellent filtration performance and anti-fouling effect. 5.5 g/l Nannochloropsis sp. have been fully retained using the fabricated membrane with average flux 28.9 L/m2h. Furthermore, the membrane demonstrated excellent anti-fouling effect owing to its higher membrane hydrophilicity (33.76o). Thus, the fabricated membrane can help to improve sustainability in algae-based production.